MONITORING OF SIGNS OF FINANCIAL AND ECONOMIC INSTABILITY OF A COMPANY – A CONDITION OF PRESERVATION OF BUSINESS - E. P. Kochetkov (Real Economics Publishing House, 2014)
This article investigates indications of approach of instability of the industrial organization on the basis of the system approach. Monitoring of these indications is considered as one of conditions of maintenance of its business. Author offers the system of indications of threat of approach of financial and economic instability of business, developed on the basis of the definition of financial and economic instability developed by the author and the conducted statistical research. This system is considered in a cut making parts of business resistibility to negative factors and strategy of its development.